Peran Ulama dan Kitab dalam Mencerahkan Umat: Kontribusi Literasi Islam - Septi, Annisa Dwi; Ahmad, Arifin; Aprilia, Jeny; Syadiah, Faza Deliani; Fauzi, Fakhri Ilham (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Literacy has been an important foundation in the development of Islamic civilisation since its early days. Scholars have played a central role as custodians, developers and disseminators of knowledge through written works in the form of books. These books not only contain religious teachings such as tafsir, hadith, fiqh, and tasawwuf, but also include general sciences, including science and philosophy. This article is a literature review that aims to examine the ulama's contribution in enlightening the ummah through literacy and highlight the role of kitab as the main medium in the inheritance and internalisation of Islamic values. Data collection techniques were conducted through library research on various primary and secondary sources, such as classical books, scholarly works and scientific journal articles. Data analysis was done descriptively-qualitatively with historical and thematic approaches, to reveal the role of literacy in the social and intellectual transformation of Muslim society. The findings of this study confirm the importance of preserving the Islamic literacy tradition and its actualisation in the modern context as a strategic strategy to educate the ummah, both spiritually and intellectually